The Role of Logistics Network Design on Service Delivery in Public Health Care Systems: A Case of National Medical Stores - Rebecca Namukwaya (Uganda Christian University, 2024)
The study investigated the role of logistics network design on service delivery in public health systems. The objectives that guided the study include; to examine the role of decentralized warehousing, to examine the role of centralized warehousing and to identify the inventory management practices used at National Medical Stores. The study employed a cross-sectional research design that was descriptive in nature with qualitative and quantitative data. Quantitative Data was analyzed using the statistical package for social sciences (SPSS) computer system program to come up with the findings. The primary data sources were National Medical Stores along with retrospective data from archives, conducted as a cross-sectional study. The study involved 40 stakeholders, with a sample size of 36 determined using Krejcie and Morgan’s method. Stratified and purposive sampling methods were used, and data was collected through questionnaires. The study findings were presented using tables. The study findings stressed that National Medical stores have effective inventory management practices but needs improvement in technology integration and optimized distribution channels. In investigating the role of Logistics Network Design on service delivery in public health care systems, several key findings emerged. National Medical stores implemented a robust centralized warehousing System and inventory management practices with clear records of stock inflows and outflows for efficient inventory management and service delivery. However, gaps existed in the implementation of a decentralized warehousing system emphasizing the need for emergency response. In conclusion, this research highlights the greater role of logistics network design on service delivery and offers recommendations to NMS towards the gaps to enhance its logistics network designs and improve service delivery in health care systems.